Problematika Kepastian Hukum Penentuan ‘Orang Tidak Mampu’ dalam Kewajiban Notaris Memberikan Jasa Cuma-Cuma - Made Putra Darma Yasa; I Wayan Novy Purwanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The obligation of notaries to provide free legal services to indigent persons, as stipulated in Article 37 paragraph (1) of the Notary Position Act, represents an effort to ensure access to justice for all members of society. However, the provision does not provide a clear definition or criteria for determining who qualifies as an “indigent person,” leading to practical and juridical issues in its implementation. This study aims to analyze the concept of “indigent persons” from a legal perspective and to examine the mechanism for determining such status in the execution of notaries’ obligations. This research employs a normative legal method using statutory and conceptual approaches, with qualitative analysis of primary and secondary legal materials. The findings indicate that the absence of an operational definition results in a vague norm that creates legal uncertainty. In practice, the determination of indigent status tends to be subjective and lacks standardized criteria, which may lead to inconsistency, potential injustice, and misuse. Furthermore, the absence of a structured determination mechanism causes the obligation to provide free legal services to be ineffective in practice. Therefore, it is necessary to establish objective and multidimensional criteria, along with an integrated determination mechanism combining administrative and factual approaches, to ensure that notaries’ obligations are implemented effectively, appropriately targeted, and capable of supporting broader access to justice for economically disadvantaged communities.